Over 250 Laparoendoscopic Single Site (LESS) Fundoplications: Lessons Learned. Issue 9 (September 2015) - Sukharamwala, Prashant; Teta, Anthony; Ross, Sharona; Co, Franka; Alvarez-Calderon, Giannina; Luberice, Kenneth; Rosemurgy, Alexander
Laparoendoscopic single site (LESS) surgery is a more recent advance in the progression of minimally invasive surgery. This study was undertaken to assess lessons learned after our first 250 LESS fundoplications for gastroesophageal reflux disease (GERD). All patients undergoing LESS fundoplications were prospectively followed from 2008 to 2014. Patients scored the frequency/severity of their symptoms before/after LESS fundoplication using a Likert scale (0 = never/not bothersome to 10 = always/very bothersome). Patients also scored satisfaction with their incision using a Likert scale (1 = revolting to 10 = beautiful). A total of 300 patients undergoing LESS fundoplication for GERD were not different by age or gender. Surgeons undertook 190 Nissen fundoplications and 110 Toupet fundoplications; 28 of which were "redo" fundoplications. Preoperative symptoms were notable, especially heartburn (frequency = 8, severity = 7). Symptoms were ameliorated postoperatively (e.g., heartburn: frequency = 0, severity = 0, P < 0.01). Postoperatively, patients scored satisfaction of their incisions with a median score of 10. Eighty-three per cent of patients were at least satisfied with their overall experience; 92 per cent would undergo the operation again knowing what they know now. Patients report significant symptom relief, high satisfaction, and excellent cosmesis after LESS fundoplication. LESS fundoplication safely ameliorates symptoms of GERD with pronounced satisfaction, in part, because of the cosmetic outcome (i.e., lack of scaring), and its application is encouraged.